2022
DOI: 10.3390/ijms231911800
|View full text |Cite
|
Sign up to set email alerts
|

ECG Markers of Acute Melatonin Treatment in a Porcine Model of Acute Myocardial Ischemia

Abstract: In myocardial ischemia, melatonin confers antiarrhythmic action, but its electrocardiographic expression is unclear. We aimed to evaluate the effects of melatonin treatment on electrocardiogram (ECG) parameters reflecting major arrhythmogenic factors and to test the association of these parameters with ventricular fibrillation (VF) incidence. Myocardial ischemia was induced by 40 min coronary artery occlusion in 25 anesthetized pigs. After induction of ischemia, 12 and 13 animals were given melatonin or placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…A similar effect of melatonin has been demonstrated in a chronic model of melatonin treatment, where melatonin modified both depolarization and repolarization processes, but only the depolarization changes were associated with the antiarrhythmic action of melatonin, while the effect on repolarization (but not on depolarization) correlated with antioxidant activity [27]. Also, the data obtained in the present study correspond to the findings in the porcine model of acute ischemia with the application of melatonin [31,32]. Collectively, the present findings suggest that the antiarrhythmic effects of melatonin were related to the changes in the depolarization process.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A similar effect of melatonin has been demonstrated in a chronic model of melatonin treatment, where melatonin modified both depolarization and repolarization processes, but only the depolarization changes were associated with the antiarrhythmic action of melatonin, while the effect on repolarization (but not on depolarization) correlated with antioxidant activity [27]. Also, the data obtained in the present study correspond to the findings in the porcine model of acute ischemia with the application of melatonin [31,32]. Collectively, the present findings suggest that the antiarrhythmic effects of melatonin were related to the changes in the depolarization process.…”
Section: Discussionsupporting
confidence: 88%
“…Acute effects of melatonin application were studied in anesthetized pigs [31,32] and ex vivo in perfused rat hearts [17]. These investigations demonstrated that melatonin reduced ventricular tachycardia and/or ventricular fibrillation (VT/VF) incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Tp-e can be measured in a single lead or from the earliest Tpeak among all leads to the latest Tend throughout all leads. The second method is often used in research studies [ 23 25 ]. Moreover, the measurement of Tp-e in multiple leads is preferred to measurement in single lead because it allows the calculation of Tp-e dispersion, which is a difference between the highest and the lowest value of Tp-e in all leads [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…As an ECG parameter, QRS was considered a predictor of left ventricular systolic dysfunction after a first STEMI by Fabiszak et al ( 29 ). Bernikova et al reported that the QRS duration prolonged after LAD occlusion ( 30 ). The QRS duration also had a special prognostic significance in NSTEMI patients ( 10 ).…”
Section: Discussionmentioning
confidence: 99%